Comparison of Digital Camera Real-Time Display with Conventional Teaching Tube for Slit Lamp Microscopy Teaching. (2nd January 2022) - Huang, Zijing; Yang, Jianling; Wang, Hongxi; Pang, Chi Pui; Chen, Haoyu
ABSTRACT: Purpose: To compare slit-lamp microscopy teaching outcomes with digital camera real-time display and conventional teaching tube in undergraduate education of clinical ophthalmology. Methods: Thirty-seven Year 4 medical students were assigned to two groups for slit lamp microscopy teaching with digital camera real-time display (n = 18) and teaching tube (n = 19). The outcome measures included a 5-item questionnaire on their experience and the quality of slit lamp photos taken by the students. Results: The overall satisfaction score was significantly higher in the group of digital camera real-time display compared with the group of teaching tube (4.5 ± 0.5 vs. 4.2 ± 0.7, P = .013). The former group also achieved higher quality score of the slit-lamp photography (4.1 ± 0.3 vs. 3.6 ± 0.5, P = .002). Conclusions: The digital camera real-time display attachment is more effective in undergraduate ophthalmic education over conventional slit-lamp teaching tube. It is also more favored by students and is thus highly recommended for clinical ophthalmology education.